Regulation of T cell apoptosis during the immune response - Baumann, Sven; Krammer, Peter H. (Current molecular medicine, 2002)
Apoptosis of T-lymphocytes is a fundamental process regulating antigen receptor repertoire selection during T cell maturation and homeostasis of the immune system. It also plays a key role in elimination of autoreactive lymphocytes. Resting mature T cells are activated by antigen to elicit an appropriate immune response. In contrast, preactivated T cells undergo activation-induced cell death (AICD) in response to TCR triggering alone. Thus, death by apoptosis is essential for function, growth and differentiation of T-lymphocytes. This review focuses on apoptosis mechanisms involved in T cell development and during the course of an immune response.
Gesehen am 03.03.2021